Early CRRT and antibiotic management in shock patient due to urosepsis with immunocompromised post renal transplantation - Sandhi Prabowo; Dita Aditianingsih (International Journal of Medical Research and Review, 2018)
Septic shock is a major cause of morbidity and mortality in the ICU. A 32-year-old patient was diagnosed with septic shock due to urosepsis, hospital-acquired pneumonia (HAP), and acute kidney injury (AKI) post renal transplantation. Continue Renal Replacement Therapy (CRRT) was performed to remove inflammation mediator. Broad-spectrum antibiotics, blood glucose control, adequate volume status, nutritional support, and temporary withdrawal of immunosuppressive drugs were ensured. Patient was stable on the 5th day, extubated by day 8th, and discharged from ICU 10 days later. It can be concluded that early CRRT could prevent organ failure and further complications caused by septic shock.